Taxminimization, Ukuran Perusahaan Dan Mekanisme Bonus Terhadap Transfer Pricing - Stiawan, Hari (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2021)
This study aims to obtain empirical evidence about the effect of Tax Minimization, Company Age and Bonus Mechanism on transfer pricing. Transfer pricing is measured using a related party transaction proxy as seen from the data contained in the sample companies' financial reports. The type of research used in this research is associative quantitative analysis. This research was conducted using data taken from the IDX in the manufacturing sector for the period 2014 - 2018. The sampling method used purposive sampling with the sample results obtained in this study were 26 companies for 5 years. The methodology used is regression using descriptive statistics, classic assumption test and multiple regression analysis. Based on the test results, it is found that Tax Minimization has no significant effect on transfer pricing. Company age has a positive effect on transfer pricing. The Bonus Mechanism has no significant effect on Transfer Pricing, and simultaneously Tax Minimization, Company Age and Bonus Mechanism have an effect on Transfer Pricing